Raltegravir with Optimized Background Therapy for Resistant HIV-1 Infection - Steigbigel, Roy T; Cooper, David A; Kumar, Princy N; Eron, Joseph E; Schechter, Mauro; Markowitz, Martin; Loutfy, Mona R; Lennox, Jeffrey L; Gatell, Jose M; Rockstroh, Jurgen K; Katlama, Christine; Yeni, Patrick; et al. (The New England journal of medicine, 2008)
For patients infected with multidrug-resistant human immunodeficiency virus type 1 (HIV-1), therapeutic options are limited. Raltegravir is a new molecule that inhibits HIV integrase. In two phase 3 studies, raltegravir was found to be superior to placebo, in the context of optimized background antiviral therapy, in suppressing HIV viral load at 48 weeks (62.1% vs. 32.9%). In two phase 3 studies, raltegravir was found to be superior to placebo, in the context of optimized background antiviral therapy, in suppressing HIV viral load at 48 weeks (62.1% vs. 32.9%). Highly active antiretroviral therapy is the standard of care for patients with advanced human immunodeficiency virus (HIV) infection. 1 Combination regimens have resulted in improved survival, decreased morbidity, and cost-effective care for patients with a CD4 count of less than 350 per cubic millimeter. 2 – 8 However, viral suppression cannot always be achieved or sustained with standard treatments because of the development of viral resistance, toxic effects of drugs, or lack of adherence. 9 – 18 The majority of HIV-infected patients in whom highly active antiretroviral therapy fails have resistant viral quasispecies. 12 – 15 , 19 , 20 Cross-resistance to agents within a drug class may exhaust . . .